Self-regulation, self-evaluation, and self-efficacy: How does its impact on employability? - Muhamad Hasan Abdillah; Fatwa Tentama; Herlina Siwi Widiana; Zurqoni Zurqoni (International Journal of Evaluation and Research in Education (IJERE), 2023)
This study investigated whether self-regulation, self-evaluation, and self-efficacy can predict students’ employability levels, either simultaneously or partially. Researchers used class XII students of Muhammadiyah 1 Bambanglipuro Vocational High School, Indonesia with the criteria of having implemented industrial work practices (N=433) as research subjects. The sample consisted of 168 students obtained randomly by cluster sampling technique. Likert model scale as the main instrument in obtaining empiric data to answer the research hypothesis using multiple regression techniques with the help of the SPSS V.23 program. Based on the results of the analysis, it is known that self-regulation, self-evaluation, and self-efficacy have a very significant effect on the level of employability (F=134.28 and sig.=.000). Partially, each independent variable (self-regulation, self-evaluation, and self-efficacy) also has a very significant effect on employability with statistical values (t) obtained at 11.54, 3.24, 7.99 and sig. level of .000, .001, .000. These findings provide evidence that self-originating factors (self-regulation, self-evaluation, and self-efficacy) are sufficiently capable of increasing employability. Thus, it can be concluded that internal factors are one of the critical factors in predicting the employability of vocational students.